usctrojanfan
New member
- Joined
- Jun 17, 2015
- Messages
- 10
Im suppose to simplify
x^-1-y^-1
__________
x^2-y^2
________ here is what i've done, x/1-1/y /(x+y(x-y)/xy i used the axd and bxc method so I got: xy/x(x+y)y(x-y)= xy/x^2+xy-xy+y^2= xy/(x+y)(x+y) The answer on the calculator says its
xy
what am I doing wrong? [FONT=MathJax_Main]−[FONT=MathJax_Math]y[/FONT][FONT=MathJax_Main]2[/FONT][FONT=MathJax_Math]x[/FONT][FONT=MathJax_Main]([/FONT][FONT=MathJax_Math]x[/FONT][FONT=MathJax_Main]+[/FONT][FONT=MathJax_Math]y[/FONT][FONT=MathJax_Main])[/FONT][FONT=MathJax_Main]([/FONT][FONT=MathJax_Math]x[/FONT][FONT=MathJax_Main]−[/FONT][FONT=MathJax_Math]y[/FONT][FONT=MathJax_Main])[/FONT][/FONT]
x^-1-y^-1
__________
x^2-y^2
________ here is what i've done, x/1-1/y /(x+y(x-y)/xy i used the axd and bxc method so I got: xy/x(x+y)y(x-y)= xy/x^2+xy-xy+y^2= xy/(x+y)(x+y) The answer on the calculator says its
xy
what am I doing wrong? [FONT=MathJax_Main]−[FONT=MathJax_Math]y[/FONT][FONT=MathJax_Main]2[/FONT][FONT=MathJax_Math]x[/FONT][FONT=MathJax_Main]([/FONT][FONT=MathJax_Math]x[/FONT][FONT=MathJax_Main]+[/FONT][FONT=MathJax_Math]y[/FONT][FONT=MathJax_Main])[/FONT][FONT=MathJax_Main]([/FONT][FONT=MathJax_Math]x[/FONT][FONT=MathJax_Main]−[/FONT][FONT=MathJax_Math]y[/FONT][FONT=MathJax_Main])[/FONT][/FONT]